2003
DOI: 10.1002/pros.10329
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p21 cell cycle protein is an independent predictor of response to salvage radiotherapy after radical prostatectomy

Abstract: The expression of p21 in prostatectomy specimens could help predict the likelihood of response to salvage radiotherapy, particularly in patients treated before PSA reaches 1 ng/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…Although histologic grading is one of the most important predictors, its usefulness is limited because the majority of cases are moderately differentiated tumors (Gleason score of 6 or 7). The multivariate input of multiple predictors has been used in nomogram format to provide the most accurate and bias-free estimates of recurrence (30,31). However, restrained input from predictor variables limits the accuracy of these tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although histologic grading is one of the most important predictors, its usefulness is limited because the majority of cases are moderately differentiated tumors (Gleason score of 6 or 7). The multivariate input of multiple predictors has been used in nomogram format to provide the most accurate and bias-free estimates of recurrence (30,31). However, restrained input from predictor variables limits the accuracy of these tools.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the cell cycle inhibitor protein p21 has been shown as an independent predictor of response to salvage radiotherapy after RP (30). Progression to androgen independence has also been correlated with p21 (31).…”
Section: Discussionmentioning
confidence: 99%
“…To generate male/female TRAMP mice with heterozygous deletion of p21/Cdkn1a (p21 +/− /TRAMP), transgenic male lines, 12,13 clinically in many cases, the elevated p21 levels in human PCa tissues have been reported to be associated with prostatic disease graded with high Gleason scores, reduced survival outcomes and increase in the recurrence of this malignancy. [14][15][16][17] On similar lines, evaluation of human PCa samples from androgen-dependent/-independent tumors and xenograft studies employing androgen-responsive cell lines have shown that increased expression of p21 is associated with high proliferative index and progression to androgenindependent PCa. 46 Given the fact that p21 is a growth inhibitory molecule, 7-9 the findings indicating toward an association of overexpression of p21 with poor outcome in PCa patients raises questions about the inhibitory role of this molecule in PCa growth and progression.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 Whereas upregulation of p21 by anticancer and chemopreventive agents has been shown to induce growth arrest in several androgen-dependent and -independent PCa cell lines, 6,12,13 in many cases, the elevated p21 levels in human PCa tissues have been correlated with higher Gleason score, poor survival and increased recurrence rate of the disease. [14][15][16][17] Interestingly, some reports have also associated high p21 levels with metastasisfree survival in PCa patients. 18 Together, these mixed and contradictory observations warrant extensive studies to examine the roles of p21 molecule in PCa progression.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction of p21 Cip1 with cyclin D1/CDK is known to promote stabilisation and nuclear import of the complex, resulting in enhanced CDK activity (Parry et al, 1999;Gladden and Diehl, 2005). Similarly, p21 Cip1 has been shown to be increased in prostate cancer and holds potential merit as a prognostic indicator (Matsushima et al, 1998;Sarkar et al, 1999;Omar et al, 2001;Rigaud et al, 2004). To determine the relevance of p21 Cip1 to cyclin D1 localisation and proliferation, p21 Cip1 immunoreactivity was assessed in a subset of patient tumours (n ¼ 16) and the three metastatic tumours wherein cyclin D1 and Ki-67 status had been determined.…”
Section: Contribution Of P21 Cip1 To Proliferation and Progression Ofmentioning
confidence: 99%